A Clinical and Laboratory Study of a Patient with an Unusual Factor VIII Inhibitor - Bloom, A.L; Davies, A.J; Rees, J.K (Thrombosis and Haemostasis, 1966)
The clinical and laboratory features of a patient with a post-partum factor VIII inhibitor are described. A large sublingual haematoma caused respiratory distress but this was quickly relieved by treatment with bovine antihaemo- philic globulin. The inhibitor activity rapidly declined possibly because of corticosteroid therapy but factor VIII levels subsequently remained reduced.Inactivation of factor VIII by the inhibitor in vitro increased on incubation but was incomplete and did not give the linear pattern described by Biggs and Bidwell (1). Although the clotting time of the patient’s blood was prolonged a factor VIII level of 18% was detected. The inhibitor was apparently more active when residual factor VIII was assayed by a one-stage than by a two- stage method and it inactivated similar proportions of factor VIII when this was added to plasma in different concentrations. Factor VIII could not be recovered from combination with the inhibitor by euglobulin precipitation. The results suggest that the inhibitor altered the reactivity of factor VIII.A transiently positive direct antiglobulin test suggested an immunological basis for the syndrome but although the inhibitor showed some species specificity for human factor VIII no other supporting evidence was obtained.